The Impact of Trust And Promotion on The Increase In Consumer Usage of The LINKAJA Application at Margomulyo Surabaya Fuel Station - Kurniawan, Taufik; , Dhiyan Septa Wihara; Nindya Kartika Kusmayati; Yuli Kurniawati; Bayu Permadi (Journal of Economics, Business, and Government Challenges, 2025)
This research aims to determine the influence of consumer trust and promotions on increasing the use of the LinkAja application at the Margomulyo gas station, Surabaya city. The population in this study were consumers at the Margomulyo gas station, Surabaya city, who made purchases using the LinkAja application. The data source used is primary data using random sampling techniques using a sample size of 100 respondents. The analytical method for this research uses multiple linear regression analysis with SPSS (Statistical Product And Service Solution) version 2.10 for Windows with multiple linear regression results Y = 5.968 + 0.209X1 + 0.2073X2 + e. The assessment results are valid and reliable, have a normative distribution, are free of heteroscedasticity, are free of multicollinearity and are free of autocollinearity. Multiple linear models were obtained. Based on the results of the analysis of the T Test results using the formula above, it is known that the magnitude of the influence of the trust impact variable on increasing the use of the LinkAja application is 0.03. Promotion of increasing interest using the LinkAja application by 0.01. Based on the results above, it can be seen that the trust variable is a variable that has a greater influence of 0.03 on increasing use of the LinkAja application. Trust will also lead to manipulative marketing because trust has a big opportunity to get customers.